نشأة الدولة الحديثة: دراسة تحليلية للتاريخ والفكر السياسي: Origins of the Modern State: An Analytical Study of History and Political Thought - Kotob, Mohamad Saleh; Ahmed Badi, Jamal (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
إن الدولة الحديثة اليوم من المسلمات السياسية حيث صار العالم مقسماً إلى 193 دولة، تزيد أو تنقص، وقد اختفت الأشكال السياسية الأخرى. ورغم كثرة ما كتب حولها والاهتمام الذي حظيت به هذه المؤسسة السياسية، العلماء والمختصون لا يملون من الاعتراف بصعوبة تحديد أصول ونشأة الدولة الحديثة. فمن المفيد البحث عن أصولها وأحداث نشأتها تاريخياً، ومن أجل أن تكتمل الصورة، يَحسن النظر كذلك في تطور الفكر السياسي حول الدولة الحديثة ومحاولة مقارنة وربط الأحداث التاريخية بتطور المواضيع والمفاهيم الفكرية، وذلك بواسطة المنهج التاريخي للأول، والمنهج التحليلي النقدي للأخير، ثم المنهج المقارن للربط والمقارنة. وتبين من البحث أن الصحيح تحديد زمن نشأة الدولة الحديثة بالحقبة المبكرة من العصر الحديث ما بين 1500م و 1800م، على اختلاف الرأي في ذلك. ومع تراجع سلطة الكنيسة الكاثوليكية الزمنية عبر عدة قرون وتسارع أفولها بعد حدث الإصلاح البروتستانتي، قويت سلطة الملوك والأمراء وبدأ مفهوم السيادة يرتبط بالحاكم الزمني. ويبدو أن الاستبداد والحكم المطلق الذي هيمن على القرن السابع عشر في أوربا، إضافة إلى كثرة الحروب، كل ذلك أدى إلى تعزيز مركزية الدول آنذاك من طريق تحسين البيرقراطية الإدارية، ووسائل التواصل والمراقبة، وزيادة قدرات الجيوش ودخلها، وكل ذلك شكل جوهر الدولة الحديثة. وبفضل حقبة التنوير وإصلاحاتها، وتطور مفاهيم الحرية وحقوق الفرد، والسيادة الشعبية، ومحاسبة السلطة وغيرها، ثم ترجمة بعض تلك المفاهيم إلى الواقع في الثورتين الفرنسية والأمريكية، كانت الدولة الأوربية قد تطورت سياسياً وإدارياً بشكل لا يمكن الرجوع عنه. ومع دخول القرن التاسع عشر، خاضت العديد من الدول الأوربية مخاض كتابة دستور الدولة وتطبيقه إلى أن تحولت أوربا برمتها إلى الحكم الدستوري، خلا روسيا. وخلافاً للرأي القائل بأن تطور الدولة الحديثة واختفاء الأشكال السياسية الأخرى كان أمراً متوقعاً بل وغائياً، تبين أن الأمر ليس كذلك، بل كان نتيجة لعوامل كثيرة؛ ومصير الدولة الحديثة مستقبلاً كذلك مرتبط بعوامل مختلفة تشبه تلك في الماضي كثرةً وتعقيداً. The modern state is a political reality today in a world divided into 193 states, subject to variation, while other political forms have disappeared. Despite the volumes that have been written about this political institution and the attention it has received, scholars and experts do not tire from admitting the difficulty of determining the origins of the modern state. Thus, it is beneficial to research its historical origins and emergence, and in order for the picture to be complete, it is expedient to analyze the development of political thought as it relates to the modern state and attempt to compare and connect the history to the development of political themes and concepts, using a historical approach for the former, and a critical, analytical approach for the latter, followed by a comparative approach for comparing and connecting the two. Despite some differences of opinion, it is correct to place the origins and emergence of the modern state in the early modern period between 1500 and 1800 C.E. As the Catholic Church’s temporal authority regressed over several centuries, and did so even quicker after the Protestant Reformation, this consolidated the temporal power of kings and princes, and the concept of sovereignty began to be associated with temporal authority. Ironically, the despotism and absolutism that dominated 17th century Europe, as well as the prevalence of wars, seemed to promote further centralization of state power through improvements in bureaucracy, methods of communication and monitoring, and increased military capacity and spending, all of which constituted the core of the modern state. Furthermore, through the Enlightenment and its reforms, coupled with the maturation of concepts in political thought like freedom and individual rights, popular sovereignty, and accountability, and later translating such concepts into reality through the French and American Revolutions, the European state had developed politically and administratively beyond the point of no return. With time, and throughout the 19th century, many European states underwent the trials of writing and implementing a state constitution until the whole of Europe eventually turned to constitutional rule, barring Russia. Finally, contrary to the opinion that the development of the modern state and the disappearance of other political forms was expected and even teleological, it appears this was not the case, but was the result of many factors; and the fate of the modern state is predicated on various factors as well, just as numerous and complicated as those in the past.